A study on the short and long run determinants of purchasing power parity in Malaysia - Abu Hassan Asari, Fadli Fizari; Miseman, Mohd Rizal; Hamid, Nurzahidah; Shamsudin, Norazidah; Mohamad, Zuraida; Jusoff, Kamaruzaman (IDOSI Publications, 2011)
Purchasing Power Parity (PPP) concept is founded on the law of one price; which is the idea that in the absence of transaction costs, identical goods will have the same price in different markets. This concept is particularly prominent in three ways; one (1) it theorizes the exchange rate determination; two (2) it can provide a reference point against which the current exchange rate can be deemed to be ''under or over-valued" relative to its PPP level; and three (3) irrespective of whether PPP will ever occur in the real world, deviations from it must be taken into account in making cross-regional comparisons of productivity. The basic idea of this study revolves around determining whether or not short- and long-run causality relationships exist between the PPP and the selected macro variables in the Malaysian context. Using annual time-series data ranging from 1977 to 2009, a time-series analysis methodology was conducted by regressing the values of PPP against four macro variables namely; Real Exchange rate, Consumer Price Index, Interest Rate and Money Supply. The study had discovered that all of the explanatory variables were related to PPP in the long-run, in which the PPP was negatively related to the Real Exchange Rate and Money Supply and positive in the case of Consumer price Index and Interest Rate. In addition to that, the PPP was also found to be Granger-caused by the Real Exchange Rate, Interest Rate and Money Supply. However, no such relation was found for Consumer Price Index. Since all of the variables were found to significantly influence the PPP, future studies could also incorporate other macro variables such as economic growth and net export into the model.